Indole butyric acid and paclobutrazol in blackberry stem cutting propagation (2024)
Blackberry is an important species among small fruits that have gained prominence in recent years in family farming in Brazil's southern and southeastern regions. Due to the lack of efficient methods in vegetative propagation, there is a need for exogenous application of growth regulators to promote root development. Therefore, the objective of this study was to evaluate the effect of indole butyric acid (IBA) and paclobutrazol (PBZ) on the rooting of stem cuttings of blackberry cv. Tupy. The cuttings were prepared with a length of 10 cm and planted in 114 cm3 tubes containing medium-sized vermiculite as substrate and conducted in a greenhouse with intermittent misting. The treatments consisted of three concentrations of IBA (500; 1,000 and 2,000 mg L-1) and PBZ (100, 200, and 400 mg mL-1) in addition to the control treatment. A completely randomized experimental design was used in a 4×4 factorial scheme, with three replicates and 10 cuttings per experimental unit. After 120 days, the percentages of rooted cuttings, callus formation, alive, dead, and sprouted cuttings, shoot length, number, length, and fresh weight of roots were evaluated. The use of plant hormones did not have a favorable effect on the propagation of blackberry cv. Tupy through stem cuttings, with inhibition of rooting observed.